Patients’ experiences with the application of medical adhesives to the skin: a qualitative systematic review protocol - Mats Eriksson; Sara Johansson; Jan Kottner; Dimitri Beeckman; Lise-Marie Kinnaer; Hannelore Hofman; Tanja Duljic; Samal Al Gilani (BMJ Open, 2023)
Introduction Medical adhesives are adhesives used in medical devices to establish and maintain contact with the body over a period of time (usually by application to the skin) and are widely used in most care settings. Application of medical adhesives to the skin can lead to skin stripping, mild or severe allergic reactions and skin irritation that may manifest as redness, itching or rash. Adhesive-related skin injury can lead to infection, delayed wound healing and an increased risk of scarring. These injuries can cause severe discomfort and pain, and can affect the patient’s quality of life. A systematic review summarising patient’s experiences on this topic will contribute to informing adhesive producers and policy makers, and guiding further development and improvement of available technologies.Methods and analysis This systematic review protocol is based on the principles of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guideline. A systematic search will be conducted in CINAHL, EMBASE, MEDLINE and PsycINFO. In addition, manual searches will be performed, reviewing the reference lists of relevant reviews and articles included for quality assessment. Qualitative studies using various methods will be considered for inclusion. Screening of title, abstract and full text will be done by two reviewers. The methodological quality of studies under consideration will be critically assessed by two reviewers using the Joanna Briggs Institute Critical Appraisal Tool for Qualitative Research. Data extraction will be performed independently by two reviewers using a predefined data extraction form. Meta-aggregation will be used to summarise the evidence.Ethics and dissemination No ethical approval or consent is required because no participants will be recruited. This systematic review protocol is published in an open access journal to increase transparency of the research methods used. Results will be disseminated at national and international conferences.